Empowering Women Victims of Domestik Violence (DV) By The Departement of Women’s Empowerment and Child Protection of Samarinda City - Dyah Fitri Ananta; Zulkifli Abdullah (Citra Media Publishing, 2026)
This study aims to describe the empowerment of women survivors of domestic violence carried out by the Women’s Empowerment and Child Protection Agency (DP3A) of Samarinda City. Empowerment is considered a crucial step in rebuilding survivors’ independence, self-confidence, and quality of life. This research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. Informants were selected using purposive sampling and consisted of domestic violence survivors as the main informants, the head of the women’s empowerment division as key informants, and staff of the Regional Technical Implementation Unit for Women and Child Protection (UPTD PPA) as supporting informants. The findings show that empowerment is implemented through three main approaches: enabling, empowering, and protecting. The enabling approach includes providing information, counseling services, education on domestic violence, and complaint facilities to build survivors’ awareness and courage. The empowering approach involves skills training, business capital assistance, strengthening economic capacity, and facilitating equivalency education to increase survivors’ independence. Meanwhile, the protecting approach includes the provision of safe houses, legal protection, psychological assistance, and cross-institutional collaboration to ensure victims’ safety and recovery. These programs contribute to improving survivors’ self-confidence, economic independence, and psychosocial resilience. However, the implementation still faces challenges such as limited budgets, a shortage of professional personnel, and persistent social stigma. This study concludes that the enabling, empowering, and protecting model implemented by DP3A Samarinda has produced positive impacts, although further strengthening is needed to ensure optimal and sustainable implementation.